Literatur Review: Perbandingan Kandungan Zat Gizi Makro & Mikro pada Daging Ayam dengan Sosis Sapi - Aisyah Fairuz; Ilma Nur Islami; Intan Mayang Sari; Ratu Raudhah Ad Daulah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Healthy food and junk food have a big impact on health. Healthy foods made from natural ingredients rich in nutrients support optimal body function and improve the immune system, as well as preventing disease. In contrast, junk food is high in calories but low in nutrients, often containing saturated fat, added sugar and excessive salt. This article was created to compare the macronutrient and micronutrient content of chicken and beef sausages. Even though both have almost the same energy content, chicken is superior in protein and minerals such as phosphorus, iron and zinc, making it a better choice for high protein intake. Meanwhile, beef sausage is higher in fat and sodium, making it risky for hypertension sufferers, even though it is rich in several vitamins B1 and E. Chicken meat is also easier to digest so it is better for digestion. The choice of both must consider the nutritional needs and health conditions of the individual